Pengenalan Database bagi Pelajar di SMA Negeri 2 Binjai - Nurhayati; Felix; Arisman; Andriansyah, R. A. Fattah (Jurnal Masyarakat Indonesia (Jumas), 2025)
One of the problems often faced in several educational institutions today is the lack of information related to scientific databases, resulting in a lack of interest in high school students in studying this field. We all know that currently Information and Communication Technology (ICT) continues to develop rapidly, both devices or machines and so on. So in the future there is the potential for the world to be flooded with latent data problems. Thus, of course, human resources are needed who have special knowledge in the desired field. One way is to prepare the current young generation to play an active role and contribute in this matter. Therefore, training solutions are needed to trigger and strengthen understanding of basic database concepts that are applied and adopt the Merdeka Belajar curriculum in class X SMA Negeri 2 Binjai so that they can overcome difficulties in understanding basic concepts, using database software and understanding data models and writing questions.